THE ARMENIAN IDENTITY IN THE CONTEXT OF DISTORTED FORMS OF INDIVIDUALISTIC AND COLLECTIVISTIC CULTURES - ZAKARYAN, SEYRAN (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
In the article the author suggests that though the individualistic culture of life arrangement prevails amongst Armenians with its horizontal and vertical relations, elements peculiar to both individualistic and collectivistic (family-centric, group-centric, party-centered) cultures and hybrid versions are present in it. Moreover, in the course of history the Armenians mostly made use of the disadvantages peculiar to those cultures than of advantages which had a negative impact on the identity characteristics and manifestations of the Armenians. Individualism has perverted over time and manifested itself mostly in the form of personidolization, and collectivism in the utmost forms of family-idolization and groupidolization, which made the behaviour of individuals contradictory and unpredictable. As a result of distorted perceptions and incomplete usages of these two cultures some elements of an obsequious and subservient political subculture, impersonal adaptability and passivity, present-oriented and beneficiary position, unvisionary way of existence, indifference toward national values and statehood, etc., have taken roots among the Armenian. For instance, the author explains the indifferent attitude of Armenians to- 14 ward the national state and power by non-regulated interpersonal relations, xenophilia, and irresponsibility as well as guidance by the lifestyle of survival and false impressions about the role of their own state, the essence, and functions of power, ruling and governance in solving national problems. In order to become a modern nation the identity traits and codes of conduct of individualistic and collectivistic cultural modes conditioned by flaws should be ’’cleared’’ from the Armenian identity as soon as possible and the outdated forms of attitude towards the highest values should be eliminated.